Robust contrast source inversion method with automatic choice rule of regularization parameters for ultrasound waveform tomography. (24th June 2016) - Lin, Hongxiang; Azuma, Takashi; Qu, Xiaolei; Takagi, Shu
Abstract: We consider ultrasound waveform tomography using an ultrasound prototype equipped with the ring-array transducers. For this purpose, we use robust contrast source inversion (robust CSI), viz extended contrast source inversion, to reconstruct the sound-speed image from the wave-field data. The robust CSI method is implemented by the alternating minimization method. An automatic choice rule is employed into the alternating minimization method in order to heuristically determine a suitable regularization parameter while iterating. We prove the convergence of this algorithm. The numerical examples show that the robust CSI method with the automatic choice rule improves the spatial resolution of medical images and enhances the robustness, even when the wave-field data of a wavelength of 6.16 mm contaminated by 5% noise are used. The numerical results also show that the images reconstructed by the proposed method yield a spatial resolution of approximately half the wavelength that may be adequate for imaging a breast tumor at Stage I.